In vitro evaluation of venom extracts of Sphecid wasps against phytopathogens of horticultural crops and mass spectrometric profiling of venom peptide components - C. Manasa; J. Jayappa; Jayashree Ugalat; Akshay Kumar; B. N. Maruthi Prasad; G. K. Ramegowda; T. B. Manjunatha Reddy; L. T. Nikita (International Journal of Tropical Insect Science, 2026)

Integrated screening of Indian slicing cucumber core genotypes for downy mildew resistance (Pseudoperonospora cubensis) and associated biochemical defence mechanisms - Kishor Varotariya; Mottaiyan Pitchaimuthu; D. C. Manjunatha Gowda; Budhavaram Varalakshmi; Kundapura V. Ravishankar; G. M. Sandeep Kumar; Vivek Hegde; Lingapatna T. Chaithra (Indian Phytopathology, 2026)

First report of Diaporthe arecae causing leaf blight in Livistona rotundifolia in India - K.N. Pallavi; M.K. PrasannaKumar; A.R. Anuvinda; R. Karan; J. Harish; Deepaka; H.V. Rame Gowda; C. Manjunatha; Pramesh Devanna; Swathi S. Patil; A.P. Mallikarjuna Gowda (Physiological and Molecular Plant Pathology, 2026)

Elucidating the molecular basis of Streptomyces antifungal activity against Fusarium verticillioides, causing maize ear and stalk rot pathogen - K.N. Pallavi; M.K. PrasannaKumar; J. Harish; R. Karan; Gopal Venkateshbabu; M. Nithish; C. Manjunatha; Deepaka; Swathi S. Patil; Aditya Narayan Sarangi (Biocatalysis and Agricultural Biotechnology, 2026)

A Review on Pharmacogenomics of Anticancer Drugs in Targeted Therapy - C. R. Chiranth; Sneha Kumkum; Sameeksha Gururaja Yellapur; Vrushali Prashant Desai; A. H. Manjunatha Reddy; Sumathra Manokaran (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Influence of larval diet on the life table traits of Chrysoperla zastrowi sillemi using age-stage two-sex life table: insights for mass production - K. T. Shivakumara; T. Venkatesan; S. S. Udikeri; M. C. Keerthi; T. Sudha; M. Mohan; C. Manjunatha; G. S. Guruprasad (Journal of Plant Diseases and Protection, 2026)

Unified Primer Enabled Detection (UPED) system for Magnaporthe oryzae infecting rice: A comparative study from conventional PCR to CRISPR Cas12a based detection systems - R. Karan; M.K. Prasannakumar; Harvinder Kour Khera; J. Harish; Swathi S. Patil; Pramesh Devanna; C. Manjunatha; Rakesh Kumar Mishra (Analytica Chimica Acta, 2026)

Influence of climatic drivers on the incidence of Thai sac brood virus (TSBV) in Apis cerana indica F. in the Western Ghats region of India - VM Chethan; AN Shylesha; MN Harish; K Aditya; S Ruqiya; KT Vijayakumar; P Jagdeesh; KT Shivakumara; C Manjunatha (International Journal of Tropical Insect Science, 2026)

In vitro hepatoprotective effects of rutin on HepG2 cells, isolated from an unexplored species: Miliusa tomentosa (Roxb.) J. Sinclair - C Inchara Moodbagil; P Meghana; Jain R Sandeep Kumar; N Prashanth; R Sharath; N.D. Satyanarayana; B Manjunatha; H Raja Naika; M.S. Savinaya; Riaz Mahmood; H.M. Kumaraswamy (Next Research, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Effect of fly-ash as filler material on mechanical and thermal properties of jute-wool-epoxy hybrid composite: prediction using artificial neural network model - Manjunatha T. S.; Shivayogi B. H.; Maruthi Prashanth B. H.; Sandeepkumar Gowda; Asif Iqbal Mulla; Girish Ariga; Divijesh Puninchathaya P; Srinivasa C. S (Journal of the Indian Academy of Wood Science, 2025)

First evidence of Corynespora cassiicola-induced disease in Chia: A new challenge for Indian Chia cultivation - H. Manjunatha; Geetha Govind; C. Channakeshava; A.S. Shashi Kiran; Prakash Koler (Physiological and Molecular Plant Pathology, 2025)

Assessment of genetic diversity and haplotype analysis of Aphis nerii (Hemiptera: Aphididae) infesting on Gymnema sylvestre in India: Insights for sustainable crop production - Shivakumara KT; Divya C; Polaiah AC; Keerthi MC; Udikeri SS; Manjunatha C; Selva Babu (Phytoparasitica, 2025)

Trichoderma spp. as a novel pathogen for maize post-flowering stalk rot in India - J. Harish; M.K. Prasannakumar; R. Karan; Gopal Venkateshbabu; N. Vamsidharreddy; K.N. Pallavi; Swathi S. Patil; Pramesh Devanna; C. Manjunatha; H.B. Mahesh (Crop Protection, 2025)

Unveiling the insecticidal gene profile of novel antifungal Bacillus thuringiensis strain NBAIR BtAr - K. Aditya; A. S. Kotasthane; C. Manjunatha; S. Nanditha; R. S. Ramya; K. T. Shivakumara; B. S. Gotyal; S. N. Sushil (Phytoparasitica, 2025)

Theobroma cacao pod shells extract mediated production of FeO nanoparticles to explore nanoadsorbent, nanofertilizer and enzyme activator applications - Vinayaka B. Shet; Sandesh Kantakere; Vibha C. Eshwarachar; Shravya Prasad Rao; Pawan Shivram Mogaveera; Poorvika Manjunatha; Keshava Joshi; Lokeshwari Navalgund; Nabisab Mujawar Mubarak (Nanotechnology for Environmental Engineering, 2025)

Plasmid profiling and bio-efficacy of Bacillus thuringiensis NBAIR BtVGa1 on Galleria mellonella L. and its biosafety on Apis cerana F. - H. S. Venu; A. N. Shylesha; S. Ruqiya; K. T. Shivakumara; S. Nanditha; B. S. Gotyal; R. S. Ramya; A. Kandan; C. Manjunatha (International Journal of Tropical Insect Science, 2025)

Prospecting indigenous Bt isolates for bioinsecticidal efficiency against soil-borne white grub, Holotrichia serrata (F.) (Coleoptera: Scarabaeidae) - M. Manoj; K. Tamilvendan; Mohan Chavan; G. Selvakumar; K. Nagaraju; C. Manjunatha (Journal of Asia-Pacific Entomology, 2025)

Molecular virulotyping and advancing the detection of Magnaporthe oryzae using a CRISPR-Cas12a-based diagnostic tool - R. Karan; M. K. Prasannakumar; Harvinder Kour Khera; J. Harish; N. Vamsidharreddy; Gopal Venkateshbabu; Pramesh Devanna; C. Manjunatha; K. B. Palanna; Rakesh Kumar Mishra (World Journal of Microbiology and Biotechnology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Development of point-of-need colourimetric, isothermal diagnostic assays for specific detection of Bacillus subtilis using shikimate dehydrogenase gene - Nanditha S.; Manjunatha C.; Shivakumara K. T.; Ramya R. S.; Kandan A.; Prasannakumar M. K.; Pramesh D.; Sushil S. N. (Folia Microbiologica, 2025)

Identification of resistant sources of castor against Fusarium wilt disease - E. Bharathi; M. Santha Lakshmi Prasad; C. Lavanya; T. Manjunatha (Genetic Resources and Crop Evolution, 2024)

Bioefficacy and molecular characterization of Bacillus thuringiensis strain NBAIR BtGa against greater wax moth, Galleria mellonella L. - H. S. Venu; A. N. Shylesha; S. Ruqiya; R. Rangeshwaran; C. Manjunatha; A. Kandan; K. S. Jagadish; G. Eswarappa; K. Aditya (Brazilian Journal of Microbiology, 2024)

Sarocladium kiliense: A first report of phytopathogenic fungus causing maize stalk rot in India - J. Harish; Gopal Venkateshbabu; M.K. Prasannakumar; R. Karan; Pramesh Devanna; C. Manjunatha (Physiological and Molecular Plant Pathology, 2024)

Host-specific development of Thrips parvispinus (Karny) (Thysanoptera: Thripidae): demography, phylogeny, and biological control prospects in India - M. C. Keerthi; N. R. Prasannakumar; V. Sridhar; C. Manjunatha; A. Mounika (Phytoparasitica, 2024)

The interaction of fungicides and nitrogen dose under two crop establishment methods influences the severity of brown spot disease in rice - D. Pramesh; A. Raghunandana; M.N. Harish; M.K. Prasanna Kumar; K.S. Sachin; M. Kiranakumara; I. Usha; M. Tulasi; D. Padma Priya; H. Pushpa; C. Manjunatha; V.P. Sunilkumar (Crop Protection, 2024)

Detection and molecular characterization of soft scale insect, Megapulvinaria maxima (Green) (Hemiptera: Coccidae) infesting Gymnema sylvestre (Retz.) R.Br. ex Sm. from India - K. T. Shivakumara; A. C. Polaiah; Sunil Joshi; M. C. Keerthi; C. Manjunatha; R. S. Ramya; B. S. Gotyal; T. N. Madhu (Phytoparasitica, 2024)

First record of tomato leaf curl Kerala virus and betasatellite associated with yellow vein mosaic disease of beet root (Beta vulgaris L. ssp. vulgaris) in India - C. N. Lakshminarayana Reddy; K. V. Ashwathappa; V. Venkataravanappa; A. Chowdappa; Shridhar Hiremath; L. Manjunatha; M. Krishna Reddy (Indian Phytopathology, 2024)

Genetic Nature and Role of Environment in Sex Expression and Phenological Characters of Pistillate Lines in Castor (Ricinus communis L.) - T. Manjunatha; K. T. Ramya; C. Lavanya; C. Sarada; S. Senthilvel; M. Yamanura; C. J. Patel; A. M. Patel; Mukesh Kumar Patel; R. Madariya; Praduman Yadav (Genetic Resources and Crop Evolution, 2024)

Stalk rot species diversity and molecular phylogeny associated with diseased maize in India - J. Harish; Gopal Venkateshbabu; M. K. Prasannakumar; Pramesh Devanna; H. B. Mahesh; D. C. Balasundara; S. Dharanendra Swamy; Sridhara G. Kunjeti; C. Manjunatha; M. E. Puneeth; H. C. Lohithaswa; Prashant P. Jambhulkar (World Journal of Microbiology and Biotechnology, 2024)

Begomovirus and DNA-satellites association with mosaic and leaf curl disease of Solanum nigrum and Physalis minima: the new hosts for chilli leaf curl virus - V. Venkataravanappa; K. V. Ashwathappa; Shridhar Hiremath; L. Manjunatha; K. S. Shankarappa; M. Krishna Reddy; C. N. Lakshminarayana Reddy (VirusDisease, 2023)

Development of interspecific hybrids through embryo rescue for heat-stable nematode resistance (Mi-9 gene) from Solanum arcanum in tomato - Suresh Reddy Yerasu; Manjunatha T. Gowda; Ram Krishna; H. C. Prasanna; Jagesh K. Tiwari; N. Rai; T. K. Behera (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploration of NMI-MsCl mediated amide bond formation for the synthesis of novel 3,5-substituted-1,2,4-oxadiazole derivatives: synthesis, evaluation of anti-inflammatory activity and molecular docking studies - B. Kulkarni; K. Manjunatha; Muthipeedika Nibin Joy; Ayyiliath Meleveetil Sajith; Sougata Santra; Grigory V. Zyryanov; C. N. Prashantha; Mohammed B. Alshammari; K. Sunil (Molecular Diversity, 2023)

Design, synthesis and molecular docking studies of some 1-(5-(2-fluoro-5-(trifluoromethoxy)phenyl)-1,2,4-oxadiazol-3-yl)piperazine derivatives as potential anti-inflammatory agents - B. Kulkarni; K. Manjunatha; Muthipeedika Nibin Joy; Ayyiliath Meleveetil Sajith; C. N. Prashantha; Ranjith Pakkath; Mohammed B. Alshammari (Molecular Diversity, 2022)

Functional analysis of SCD1 gene involved in pathogenicity of spot blotch disease of wheat causing fungus Bipolaris sorokiniana - Kartar Singh; Rashmi Aggarwal; Praveen Kumar Verma; Sandhya Verma; Sapna Sharma; C. Manjunatha; Manoj Choudhary; Deepika Kulshreshtha; Kirti Rawat (Indian Phytopathology, 2022)

Molecular and phenotypic analysis reveals cross infection of Bipolaris species in wheat and rice - Kartar Singh; Rashmi Aggarwal; Sapna Sharma; Malkhan Singh Gurjar; C. Manjunatha; Manoj Choudhary (Indian Phytopathology, 2021)

Use of single seed descent versus pedigree selection for development of elite parental lines in castor (Ricinus communis L.) - C. Lavanya; B. Ushakiran; C. Sarada; T. Manjunatha; S. Senthilvel; K. T. Ramya; M. Santhalakshmi Prasad (Genetic Resources and Crop Evolution, 2021)

Molecular Modelling and Insilico Engineering of PapMV-CP Towards Display and Development of Capripox Viral Like Particles Based on Immunogenic P32 Envelop Protein is the Homologous of the Vaccinia-Viral H3L Gene: An Insilico Approach - Burranboina Kiran Kumar; K. M. Kumar; G. B. Manjunatha Reddy; Sunil Abraham; R. Yogisharadhya; C. N. Prashantha (International Journal of Peptide Research and Therapeutics, 2020)

Genetic analysis of maydis leaf blight resistance in subtropical maize (Zea mays L.) germplasm - B. Jeevan; Robin Gogoi; Devender Sharma; C. Manjunatha; H. Rajashekara; Dama Ram; K. K. Mishra; M. G. Mallikarjuna (Journal of Genetics, 2020)

Correction to: Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Bio-priming of rice seeds with novel bacterial strains, for management of seedborne Magnaporthe oryzae L. - Narayanappa Amruta; M. K. Prasanna Kumar; Hemanth Kumar Kandikattu; G. Sarika; M. E. Puneeth; H. P. Ranjitha; K. Vishwanath; C. Manjunatha; D. Pramesh; H. B. Mahesh; S. Narayanaswamy (Plant Physiology Reports, 2019)

Development of PCR and loop mediated isothermal amplification assay for the detection of bakanae pathogen Fusarium fujikuroi - Sunil Kumar Sunani; Bishnu Maya Bashyal; Kirti Rawat; C. Manjunatha; Sapna Sharma; G. Prakash; S. Gopala Krishnan; A. K. Singh; Rashmi Aggarwal (European Journal of Plant Pathology, 2019)

Phenotypic and physiological characterization of maize inbred lines resistant and susceptible to maydis leaf blight - C. Manjunatha; Robin Gogoi; Bhupinder Singh; B. Jeevan; S. N. Rai; Pradeep Kumar Singh (Indian Phytopathology, 2019)

Aster Mapping of Limestone Deposits and Associated Lithounits of Parts of Chikkanayakanahalli, Southern Part of Chitradurga Schist Belt, Dharwar Craton, India - H. T. Basavarajappa; L. Jeevan; S. Rajendran; M. C. Manjunatha (Journal of the Indian Society of Remote Sensing, 2019)

A fingertip force prediction model for grasp patterns characterised from the chaotic behaviour of EEG - Rinku Roy; Debdeep Sikdar; Manjunatha Mahadevappa; C. S. Kumar (Medical & Biological Engineering & Computing, 2018)

Development and validation of loop mediated isothermal amplification based detection assay for Puccinia striiformis f. sp. tritici causing stripe rust of wheat - Rashmi Aggarwal; S. Sharma; C. Manjunatha; S. Gupta; V. K. Singh (Australasian Plant Pathology, 2017)

Gene-based analysis of Puccinia species and development of PCR-based marker to detect Puccinia striiformis f. sp. tritici causing yellow rust of wheat - Rashmi Aggarwal; Sapna Sharma; Sangeeta Gupta; C. Manjunatha; Vaibhav K. Singh; Deepika Kulshreshtha (Journal of General Plant Pathology, 2017)

Correlation of inducible nitric oxide synthase (iNOS) inhibition with TNF-α, caspase-1, FasL and TLR-3 in pathogenesis of rabies in mouse model - B. P. Madhu; K. P. Singh; M. Saminathan; R. Singh; A. K. Tiwari; V. Manjunatha; C. Harish; G. B. Manjunathareddy (Virus Genes, 2016)

Genetic Confirmation and Field Performance Comparison for Yield and Quality Among Advanced Generations of Erianthus arundinaceus, E. bengalense and Saccharum spontaneum Cyto-Nuclear Genome Introgressed Sugarcane Intergeneric Hybrids - Ravinder Kumar; C. Appunu; A. Anna Durai; M. N. Premachandran; V. Raffee Viola; Bakshi Ram; C. Mahadevaiah; Mintu Ram Meena; T. Manjunatha (Sugar Tech, 2015)

Impact of Long-Term Application of Domestic Sewage Water on Soil Properties Around Hubli City in Karnataka, India - Bincy K. Varkey; G. S. Dasog; Suhas Wani; K. L. Sahrawat; Manjunatha Hebbara; C. R. Patil (Agricultural Research, 2015)

Isolation of a Neurotoxin (?-colubritoxin) from a Nonvenomous Colubrid: Evidence for Early Origin of Venom in Snakes - Bryan G. Fry; Natalie G. Lumsden; Wolfgang Wster; Janith C. Wickramaratna; Wayne C. Hodgson; R. Manjunatha Kini (Journal of Molecular Evolution, 2003)